2017
DOI: 10.1111/adb.12517
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine self‐administration reverses cognitive deficits in a rat model for schizophrenia

Abstract: High comorbidity between schizophrenia and tobacco addiction has been well established. Explanatory theories include nicotine as a cognitive enhancer ameliorating symptoms of schizophrenia and underlying shared substrates increasing susceptibility to addiction in these individuals. To test these non-mutually exclusive theories, the maternal immune activation (MIA) model was utilized. To this end, pregnant Sprague Dawley rats were subcutaneously injected with a bacterial endotoxin, lipopolysaccharide (0.5 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…46 Moreover, while the maternal immune activation model also did not alter NIC self-administration, NIC self-administration did mitigate cognitive deficits observed in maternal immune activation animals, lending further support for a self-medication hypothesis. 21 Additionally, mice with a mutation commonly observed in human SCZ patients in CHRNA5, which codes for the α5 subunit of the nicotinic receptor, demonstrated cortical hypofunction that could be normalized with chronic NIC delivery. 47 This diversity of findings may reflect differences in the elements of SCZ pathophysiology captured by each particular model and their impact on the effects of NIC, as well as limitations in certain experimental designs.…”
Section: Studies Of Nic In Other Animal Models Of Sczmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Moreover, while the maternal immune activation model also did not alter NIC self-administration, NIC self-administration did mitigate cognitive deficits observed in maternal immune activation animals, lending further support for a self-medication hypothesis. 21 Additionally, mice with a mutation commonly observed in human SCZ patients in CHRNA5, which codes for the α5 subunit of the nicotinic receptor, demonstrated cortical hypofunction that could be normalized with chronic NIC delivery. 47 This diversity of findings may reflect differences in the elements of SCZ pathophysiology captured by each particular model and their impact on the effects of NIC, as well as limitations in certain experimental designs.…”
Section: Studies Of Nic In Other Animal Models Of Sczmentioning
confidence: 99%
“…However, maternal immune activation animals did not differ in self-administration from controls, except at a single dose with a high response requirement. 21 A study by Berg et al 22 using the neonatal ventral hippocampal lesion (NVHL) model of SCZ found that lesioned animals selfadminister more NIC than controls only at a moderate dose of NIC. These limited positive results are complicated by the inclusion of daily subcutaneous injections of saline or NIC during the adolescent period.…”
Section: Introductionmentioning
confidence: 99%
“…LPS treatment during gestation facilitates intravenous nicotine self-administration at higher reinforcement schedules (i.e. FR5, not FR1/FR2), but has no subsequent effects on dose-response responding or motivation for nicotine under a progressive ratio [100]. Similarly, in the MAM rat model of schizophrenia, Weeks and colleagues found no differences between MAM rats and controls in nicotine selfadministration [101].…”
Section: Nicotinementioning
confidence: 99%
“…Cognitive deficits in rats prenatally treated with LPS are ameliorated by chronic nicotine self-administration, compared to LPS rats which self-administer saline [100]. This may indicate a restoration of deficits in nicotinergic α7 and α4β2 receptor subtype function in LPS treated rats; however, this has not been assessed experimentally [100]. The effects of acute or chronic nicotine in neurodevelopmental models (e.g.…”
Section: Nicotinementioning
confidence: 99%
“…Poly I:C (see Meyer 2014 for a review) and also with LPS exposure (Fortier et al, 2007;Romero et al, 2010;Simões et al, 2018;Swanepoel et al, 2018;Waterhouse et al, 2018;Wischhof et al, 2015) although some variables such as the species used (Imai et al, 2018), the prenatal period at which exposure occurs (Waterhouse et al, 2018) Figure 1, PUS seems to be counteracting LPS effects to some extent. Therefore, a stronger effect of LPS exposure might be needed to obtain a main effect of the maternal immune activation or an interaction between both factors.…”
Section: Glutamine Levels Were Reduced In the Left Striatum By Prenatmentioning
confidence: 99%